2020
DOI: 10.3390/molecules25143110
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Ampicillin and Amoxicillin with Mn2+: A Speciation Study in Aqueous Solution

Abstract: A potentiometric and UV spectrophotometric investigation on Mn2+-ampicillin and Mn2+-amoxicillin systems in NaCl aqueous solution is reported. The potentiometric measurements were carried out under different conditions of temperature (15 ≤ t/°C ≤ 37). The obtained speciation pattern includes two species for both the investigated systems. More in detail, for system containing ampicillin MLH and ML species, for that containing amoxicillin, MLH2 and MLH ones. The spectrophotometric findings have fully con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…For this reason, determining constants under different ionic strengths is crucial to simulate real fluid conditions. Starting from the knowledge of the formation constant values at different temperatures, the enthalpy change values were calculated by using the following van’t Hoff equation: log nobreak0em0.25em⁡ β italicT = log nobreak0em0.25em⁡ β θ + normalΔ H 0 ( 1 / θ 1 / T ) italicR nobreak0em0.25em⁡ ln nobreak0em.25em⁡ 10 where log β T is the stability constant at a certain temperature (expressed in kelvin), while log β θ is the stability constant at t = 298.15 K, and R is the universal gas constant expressed as 8.314 J K –1 mol –1 . The values of formation enthalpy changes of all of the species of Cu 2+ –L and Zn 2+ –L systems are collected in Table , together with entropy and free energy values.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, determining constants under different ionic strengths is crucial to simulate real fluid conditions. Starting from the knowledge of the formation constant values at different temperatures, the enthalpy change values were calculated by using the following van’t Hoff equation: log nobreak0em0.25em⁡ β italicT = log nobreak0em0.25em⁡ β θ + normalΔ H 0 ( 1 / θ 1 / T ) italicR nobreak0em0.25em⁡ ln nobreak0em.25em⁡ 10 where log β T is the stability constant at a certain temperature (expressed in kelvin), while log β θ is the stability constant at t = 298.15 K, and R is the universal gas constant expressed as 8.314 J K –1 mol –1 . The values of formation enthalpy changes of all of the species of Cu 2+ –L and Zn 2+ –L systems are collected in Table , together with entropy and free energy values.…”
Section: Resultsmentioning
confidence: 99%
“…The protonation and formation constants values acquired at the three different temperatures of 15, 25, and 37 °C, listed in Table 1 , were used to study their dependence on temperature, as already shown for several systems [ 51 , 52 ]. The data obtained by the potentiometric measurements were analyzed using the following van’t Hoff equation: logβ T = logβ θ + Δ H 0 (1/θ − 1/ T ) R ln 10 where logβ T is the stability constant at a certain temperature (expressed in kelvin), while logβ θ is the stability constant at t = 298.15 K, and R is the universal gas constant expressed as 8.314 J K −1 mol −1 .…”
Section: Resultsmentioning
confidence: 99%
“…To experimentally evaluate the acid-base behavior of levofloxacin under different pH values, UV-spectrophotometric titrations have been performed, following procedures already reported. [51][52][53][54] Measurements on solutions containing different concentrations of the ligand at different ionic strength values were carried out, varying the pH in the range 3 r pH r 10.5. Levofloxacin absorbs between 250 and 400 nm with two maxima at about 290 and 330 nm.…”
Section: Resultsmentioning
confidence: 99%